The combination of Chinese and Western Medicine in the management of rheumatoid arthritis: A real-world cohort study across China - Zhong, Linda LD.; Wang, Rongsheng; Lam, Wai Ching; Zhu, Qi; Du, Peipei; Cao, Pei Hua; Jiang, Ting; Zhang, Yuan Yuan; Shen, Jie; Su, Xiao; Xue, Luan; Mao, Jianchun; et al. (Frontiers in Pharmacology, 2022)
Objective: To investigate the efficacy of Integrative medicine (IM), compare with Western medicine (WM), in the treatment of rheumatoid arthritis (RA) in a cohort study. Methods: This is a cohort study with recruitment of RA patients from 10 hospitals in China. The primary outcome was change in disease activity score 28 (DAS28) during 4 follow-up visits. Generalized estimating equation (GEE) models that controlled for variables were used to investigate a time trend and assess group differences in the primary outcome and secondary outcomes after propensity score matching (PSM). Results: A total of 3195 patients with RA received IM (n = 1379, 43.2%) or WM (n = 1816, 56.8%). Following 1:1 propensity score matching, 1,331 eligible patients prescribed IM were compared to 1,331 matched patients prescribed WM. The GEE analysis with PSM showed that the IM was more beneficial to significantly decrease the levels of VAS, PGA and PhGA (VAS: odds ratio (OR), 0.76; 95% CI, 0.63–0.92; p = 0.004; PGA: OR, 0.76; 95% CI, 0.64–0.92; p = 0.007; and PhGA: OR, 0.77; 95% CI, 0.64, 0.93; p = 0.004), and reduce DAS28 (OR, 0.84; 95% CI, 0.73–0.98; p = 0.030) in the per-protocol population. Conclusion: This study suggests that compare to WM, IM has advantages in improving RA-related outcomes. However, the statistical significance might not reveal significant clinical difference. Further studies should be focused on specific treatment strategies and/or disease stages.